Bronchospasm and its biophysical basis in airway smooth muscle - Fredberg, Jeffrey J (BioMed Central, 2004)
Airways hyperresponsiveness is a cardinal feature of asthma but remains unexplained. In asthma, the airway smooth muscle cell is the key end-effector of bronchospasm and acute airway narrowing, but in just the past five years our understanding of the relationship of responsiveness to muscle biophysics has dramatically changed. It has become well established, for example, that muscle length is equilibrated dynamically rather than statically, and that non-classical features of muscle biophysics come to the forefront, including unanticipated interactions between the muscle and its time-varying load, as well as the ability of the muscle cell to adapt rapidly to changes in its dynamic microenvironment. These newly discovered phenomena have been described empirically, but a mechanistic basis to explain them is only beginning to emerge.